Competency Development for Animal Handlers : Human Resource Perspective - Endah Turiasih; Asropi Asropi; Edy Sutrisno (International Journal of Economics Development Research (IJEDR), 2024)
This research aimed to develop the competence of animal handlers at Ditpolsatwa Korsabhara Baharkam Polri in animal care and to recommend a training design model for enhancing this competence. Using a qualitative research approach, the study found that while Ditpolsatwa is well-recognized and has improved in personnel, material, and facilities, the competence of animal handlers in providing first aid for animal health is minimal, relying heavily on veterinarians. Current knowledge of animal care among handlers is basic and passed down generationally. To improve performance, it is essential to enhance animal handlers' skills through targeted training. The study suggests using the ADDIE model to design training programs that enable handlers to provide first aid, manage animal health, and perform post-treatment and physical care independently.